2020
DOI: 10.1039/c9ta11167k
|View full text |Cite
|
Sign up to set email alerts
|

An antimonene/Cp*Rh(phen)Cl/black phosphorus hybrid nanosheet-based Z-scheme artificial photosynthesis for enhanced photo/bio-catalytic CO2 reduction

Abstract: A biomimicking Z-scheme photocatalytic system was constructed using dual-functionalized polymer covalent cross-linking electron mediator to catenate antimonene and black phosphorus nanosheets.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
44
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 75 publications
(44 citation statements)
references
References 40 publications
0
44
0
Order By: Relevance
“…4f ). So, the CBs of bulk VMT and FCL-PEG NSs were calculated to be −0.4 and −0.6 eV, the differences between the corresponding E g s and VBs 50 , 51 . Therefore, as schematically illustrated in Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…4f ). So, the CBs of bulk VMT and FCL-PEG NSs were calculated to be −0.4 and −0.6 eV, the differences between the corresponding E g s and VBs 50 , 51 . Therefore, as schematically illustrated in Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…It is reported that the large overpotential and the low current density and stability have made it difficult to satisfy commercial demands [20]. The biocatalyzed artificial photosynthesis system is also still being studied, as the majority of the existing semiconductors or organic photocatalysts have low light absorption ability and reduction/oxidation potentials [21]. In this paper, the multi-enzymatic cascade conversion of CO 2 in EMRs, electrochemical cells and photocatalytic reactor systems will be reviewed and the performance of each enzyme reactor system will be compared by observing the biocatalytic productivity attained by each system.…”
Section: Formate Dehydrogenase Catalyzing Co2 Reductionmentioning
confidence: 99%
“…The large surface area hold by the 2D-layered material could provide more surface active sites and superior electron mobility for the photocatalytic reaction. Recently, Ji et al successfully utilized a Z-scheme-based photocatalytic system to catalyze the biocatalytic reduction of CO 2 to CHOOH [21]. With the utilization of hybrid black phosphorus (BP) and antimonene (AM) ultrathin nanosheets and the application of the Z-scheme electron transfer mechanism, the photocatalytic system is able to improve the separation efficiency of the electron-hole pairs, resulting in high redox potentials for the photochemical regeneration of NADH.…”
Section: Challenges and Limitations Of Biocatalytic Co 2 Reduction In Photocatalytic Reactorsmentioning
confidence: 99%
See 1 more Smart Citation
“…43,44 Obviously, the thermoelectric e ciency not only relates to physicochemical properties of TE materials, such as Seebeck coe cient, electrical conductivity, and thermal conductivity, but it also has a linear correlation with the operating temperature, in which higher temperature endows more effective electron-hole pairs separation and higher thermoelectric e ciency, which is also the main obstacle for applications in biomedical elds of TE materials. 45 Based on our previous studies, [46][47][48][49][50] heterojunction construction, including p-n junction and Z scheme junction, has been demonstrated as an e cient strategy for improving electron-hole pairs separation and enhancing the catalytic e ciency. After contacting of p-type and n-type semiconductors, the interfacial electric eld will be constructed, in which the separated electrons and holes in both semiconductors would transfer in the opposite direction and locate in different semiconductors.…”
Section: Introductionmentioning
confidence: 99%